EFEKTIFITAS PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN REALISTIC MATEMATIC EDUCATION (RME ) TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA SISWA SD - Achmad Achmad; Irmansyah (Jurnal Pendidikan, 2011)
The research purpose was to describe the successfulness of Realistic Mathematic Education Model which was based on the completion aspect of students learning result, students activity level, teachers ability to manage learning, and students response toward the model applied in this research. This research was conducted toward the third year students of SD Islam Terpadu which consist of 25 students. In gathering data, pen and paper test technique was used to measure students achievement. Observation was done to know students activities and teachers ability in manage learning.Questioner was also given to know the students perceptions toward the model applied. Statistic and descriptive analysis were used to analyze the data. The research finding showed that the students activities were not effective, while the teachers ability in managing learning was effective. In the end, standard for students achievement were not reached. On the other hand, students responses toward the model applied were positive.